Development of wind-energy modeling technology and standards - Cong Wang; Yan Li; Yiwen Fan; Yongning Chi; Hongchang Qi; Hongzhi Liu (Global Energy Interconnection, 2022)
To ensure the stable operation of power systems with large proportions of wind power, China has published a series of national, industry, and enterprise standards for wind power. The increase in the number of standards and the expansion of their application scope have given rise to a situation where multiple standards overlap and conflict with regard to the establishment of models and their applicability, resulting in unclear standard application scenarios. Therefore, it is imperative to analyze the development of wind-turbine and wind-farm modeling, along with the relevant standards. This paper presents the methods for wind-turbine modeling, the equivalent model of wind farms based on the general model of wind turbines, and the technical provisions and application scenarios involved in the relevant domestic and international standards. The adaptability of the relevant standards is examined. The results of this study are helpful for advancing wind power generation in China and ensuring the safe and stable operation of large-scale wind power systems.